Pemanfaatan Artificial Intelligence (AI) Pada Penyusunan Aksi Nyata Platform Merdeka Mengajar di SDN Medalkrisna 01 - Sari, Rafika; Sari, Ratna; Ramdhania, Khairunnisa Fadhilla; Juhanda (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
This training program is designed to enhance the competency of elementary school teachers in developing practical actions on the Merdeka Mengajar Platform (PMM) by utilizing Artificial Intelligence (AI) technology. Through the use of Turnitin for plagiarism checks and Gamma for document preparation, the program aims to ensure that the work produced is original and well-structured. The training involves teachers in intensive sessions that include the introduction and use of Turnitin to detect plagiarism, as well as Gamma to assist in preparing practical action documents that meet Kemendikbud's validation standards. The results of the training show a significant improvement in teachers' ability to produce creative, innovative, and compliant practical actions according to the assessment criteria. Teachers participating in this program can produce more professional and plagiarism-free documents, thanks to the constructive feedback from AI. Furthermore, the resulting practical action documents have a clear and attractive structure, facilitating the validation process. This program also encourages the formation of a learning community among teachers, where they share best practices and support continuous improvement. Thus, this training program not only enhances teachers' digital competence but also contributes to the overall improvement of education quality. The use of AI in education becomes an important step in preparing teachers to face challenges in the digital era.